Prevention of Type 2 Diabetes through Sardines Consumption: An Integrative Review. (1st November 2022) - Díaz-Rizzolo, Diana A.; Miro, Anna; Gomis, Ramon
ABSTRACT: There are many studies regarding stop the progression to type 2 diabetes (T2D) through dietary control but there is no global recommendation for a specific diet. The strongest evidence is weight control through nutritional education but it does not include elderly people because of the risk of malnutrition that would entail. Therefore, the search for specific foods that can help slow down the progress towards T2D are of great interest. Although the controversy between fish consumption and the risk of developing T2D, it has been observed that oily fish could play a protective role. This type of fish may contain large amounts of persistent organic pollutants (POPs) but, on the contrary, contain omega-3 with effects on the cardiovascular system. In addition, the presence of taurine, a semi-essential amino acid very present in oily fish and which has been studied its antidiabetogenic effect, could play an essential role in the protective effect of this type of fish against T2D. Among them, the one with the highest concentrations of omega-3 and taurine as well as low concentration of POPs is sardine. An integrative review of observational studies and clinical trials was performed to investigate the association between sardine consumption and T2D prevention.